The Role of Different Forms of Capital in Starting and Developing an Entrepreneurial Venture: The Case of Entrepreneurs in The Beauty Services Industry - Tamara SMAGUC; Sara CIKAC (Communications of International Proceedings, 2022)
The paper discusses the role of different forms of capital in starting an entrepreneurial venture from the perspective of Croatian entrepreneurs in the beauty services industry. The research presented in this paper aimed to examine how economic capital (financial and material assets), human capital (knowledge and skills), and social capital (connections, acquaintances, and formal networks) of an individual influence the entry into entrepreneurship and enterprise development. After the theoretical review, the second part of the paper presents the role of economic, human, and social capital in entrepreneurship through the presentation of research results based on a qualitative inquiry. Primary data was collected through interviews with entrepreneurs operating in Međimurje County (Republic of Croatia). The industry in which the research was conducted refers to hairdressing salons and beauty salons (activity class S9602 according to the National Classification of Activities - NKD 2007). The collected primary data was processed by coding techniques. It is concluded that economic, social, and human capital significantly influence the nature of the business start-up process in the beauty services industry.
Keywords: capital; entrepreneurial venture; beauty services industry